Contemporary perspectives on the Australian doctorate: framing insights to guide development. Issue 6 (18th September 2020) - Coates, Hamish; Croucher, Gwilym; Moore, Kenneth; Weerakkody, Umesha; Dollinger, Mollie; Grosemans, Ilke; Bexley, Emmaline; Kelly, Paula
ABSTRACT: The growth of the doctorate in recent decades has spawned concerns about programme quality and external relevance. This article reports findings from research conducted in Australia that was shaped by the view that the doctorate remains in need of educational clarification and design. The research generated insights that can be used to modernise and realign the doctorate. First, this article discusses the development of a doctoral education framework. Next, it presents results from a questionnaire developed using the framework and administered in a national survey to both five-year-out doctoral graduates and to doctoral experts. This identifies the need to design programmes that better orient and align research training with students' professional aspirations, incorporate more real-world forms of learning, enhance traditional aspects of research training and provide structured reports of doctoral outcomes, experiences and preparations. The results underpin the need for more specific analyses of outcomes and assessment, the nature and distribution of doctoral experiences and the design and management of the resources that go into doctoral education.